2017
DOI: 10.1080/13803395.2017.1347606
|View full text |Cite
|
Sign up to set email alerts
|

Right hemispatial ipsilesional neglect with chronic right hemisphere strokes

Abstract: Although spatial neglect is more severe in contralesional than ipsilesional hemispace in the period immediately following a stroke, over time patients with RHD may develop ipsilesional neglect that is more severe in ipsilesional than contralesional space. The mechanism underlying this bias is not known and may be related to attempted compensation or the development of a contralateral attentional/intentional grasp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…However, in the focal condition of the present study, healthy controls deviated their bisection significantly more rightwards than did the patients when the shorter segment was on the right. Thus, this result suggests that the mechanism of the visuospatial attentional changes seen in patients undergoing hemodialysis seems similar to that of the ipsilesional neglect observed in patients with right frontal-subcortical lesions (Bonato et al, 2019;Harciarek et al, 2012;Kim et al, 1999;Sacchetti et al, 2015;Williamson et al, 2018). Specifically, this result from the focal condition of this study is consistent with the right hemisphere approach-avoidance theory proposed by Denny-Brown and Chambers (1958) that posits that, within the right hemisphere, the injury to the frontal lobe releases the approach-related behaviors that increase the allocation of attention to the contralateral portion of the line.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, in the focal condition of the present study, healthy controls deviated their bisection significantly more rightwards than did the patients when the shorter segment was on the right. Thus, this result suggests that the mechanism of the visuospatial attentional changes seen in patients undergoing hemodialysis seems similar to that of the ipsilesional neglect observed in patients with right frontal-subcortical lesions (Bonato et al, 2019;Harciarek et al, 2012;Kim et al, 1999;Sacchetti et al, 2015;Williamson et al, 2018). Specifically, this result from the focal condition of this study is consistent with the right hemisphere approach-avoidance theory proposed by Denny-Brown and Chambers (1958) that posits that, within the right hemisphere, the injury to the frontal lobe releases the approach-related behaviors that increase the allocation of attention to the contralateral portion of the line.…”
Section: Discussionsupporting
confidence: 66%
“…There may be several phenomena contributing to these results. For example, in healthy older people, pseudoneglect diminishes and further, healthy older people are more accurate in both tasks that elicit leftward biases and tasks that elicit rightward biases (Williamson et al, 2018). Thus, it may be that patients with ESRD are more similar to older adults, potentially due to the disease/treatment-related accelerated brain aging.…”
Section: Discussionmentioning
confidence: 99%
“…Since the majority of studies did not report spatial biases separately for male and female participants, we also calculated the percentage of male participants in each study where this data was available. Nineteen studies did not report the sex of their participants and the data from the following studies were therefore not included in this analysis: (Andrews et al 2017;Barton et al 1998;Binetti et al 2011;Corazzini et al 2005;Daini et al 2008;Doricchi et al 2002;Gassama et al 2011;Grossi et al 1999;Hatin et al 2012;Luauté et al 2012;Mennemeier et al 1997Mennemeier et al , 2001Plummer et al 2006;Richard et al 2004;Striemer and Danckert 2010;Vallar et al 2000;Veronelli et al 2014b;Williamson et al 2018;Zeller and Hullin 2018).…”
Section: Moderatorsmentioning
confidence: 99%
“…In other cases, the standard deviation was calculated first from reported confidence intervals (Andrews et al 2017) or standard errors (Plummer et al 2006;Striemer and Danckert 2010;Williamson et al 2018) before proceeding to the effect size calculation. The rationale for the decisions taken in each study are reported in Table 1.…”
Section: Effect Size Estimatesmentioning
confidence: 99%
See 1 more Smart Citation